Peran Kepemimpinan Lokal Dalam Pengembangan Wisata Bahari di Sungai Pisang Kota Padang - Surya Ramadhan; Aldri Frinaldi (Jurnal Teori dan Riset Administrasi Publik, 2024)
Local leadership is leadership that exiist is an particular community group such as customary cultural and religious similarities. in this case local leadership responsible for the development of marine tourism in the Sungai Pisang is still not optimal, it can be seen that there is still a lot of wastle thrown by the community and tourist to Sungai Pisang beach area the absences of a pier that can support the safety and comfort of tourist and the absences of rules that can regulate and discipline fishermen created by local leadership in the development of marine tourism on the Sungai Pisang